2010
DOI: 10.1002/dvdy.22264
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of TALE family transcription factors during avian development

Abstract: The TALE family of homeodomain containing transcription factors consists of the Meis, Prep and Tgif, and the Pbx subfamily of proteins. Several TALE orthologues have been identified in amniotes, but no comprehensive analysis of their expression pattern during embryogenesis has been performed. Here, we report on TALE gene expression in the avian embryo. During embryonic development, Pbx genes are predominantly expressed in the neural ectoderm and paraxial mesoderm, although Pbx3 is restricted to the intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 75 publications
5
21
1
Order By: Relevance
“…We observed that from HH5 onward precardiac mesodermal (pm) cells expressed both genes, in a pattern similar to that shown by the pm marker gene Nkx2.5 (Schultheiss et al, 1997). These data corroborate and expand previous reports (e.g., Coy and Borycki, 2010), whose analysis was restricted to only one stage, at around HH4-HH5. Moreover, we did not find Meis2 expression at Hensen's node at any gastrulation stage analyzed, in contrast with what was reported by those authors at HH5.…”
Section: Meis Gene Expression During Gastrulation and Early Neurulationsupporting
confidence: 92%
See 4 more Smart Citations
“…We observed that from HH5 onward precardiac mesodermal (pm) cells expressed both genes, in a pattern similar to that shown by the pm marker gene Nkx2.5 (Schultheiss et al, 1997). These data corroborate and expand previous reports (e.g., Coy and Borycki, 2010), whose analysis was restricted to only one stage, at around HH4-HH5. Moreover, we did not find Meis2 expression at Hensen's node at any gastrulation stage analyzed, in contrast with what was reported by those authors at HH5.…”
Section: Meis Gene Expression During Gastrulation and Early Neurulationsupporting
confidence: 92%
“…Next, we examine the transcriptional diversity of Meis genes during development, in different embryonic tissues and regions of the central nervous system (CNS). Finally, we analyze the tissue distribution of Meis1/2 mRNAs in chicken embryos during early embryogenesis and organogenesis, using in situ hybridization (ISH) on whole-mounts and cryostat sections with chicken cold-labeled RNA probes, extending and complementing recent reports (Coy and Borycki, 2010). In particular, we focus on the comparison of Meis1 and Meis2 gene expression patterns in the chicken, confronting our results with previously published data from other vertebrates.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations